Indirect Flow Injection Spectrophotometric and Chromatographic Methods for the Determination of Mebendazole in Pharmaceutical Formulations - Idrees F. Al-Momani; Raghad I. Al Souqi (مجلة بغداد للعلوم, 2023)
Chromatographic and spectrophotometric methods for the estimation of mebendazole in pharmaceutical products were developed. The flow injection method was based on the oxidation of mebendazole by a known excess of sodium hypochlorite at pH=9.5. The excess sodium hypochlorite is then reacted with chloranilic acid (CAA) to bleach out its color. The absorbance of the excess CAA was recorded at 530 nm. The method is fast, simple, selective, and sensitive. The chromatographic method was carried out on a Varian C18 column. The mobile phase was a mixture of acetonitrile (ACN), methanol (MeOH), water and triethylamine (TEA), (56% ACN, 20% MeOH, 23.5% H2O, 0.5% TEA, v/v), adjusted to pH = 3.0 with 1.0 M hydrochloric acid. Naphazoline nitrate was used as an internal standard. The absorption of mebendazole was measured using a variable wavelength UV detector at 290 nm. Linearity was obtained in the concentration range of 1-60 and 0.10-3.0 mg/L for the HPLC and FIA, respectively. The methods were applied successfully for the assay of mebendazole in pharmaceutical products and no interferences were observed from the common excipients usually used. The proposed methods were validated for their accuracy and precision.